Short Answers (Explanation in next section below)
Reason A: Given
Reason B: Angle Addition Postulate
Reason C: Substitution Property
Reason D: Subtraction Property of Equality
----------------------------------------------------------
Further Explanation:
Reason A: At the very top of the problem, it states "given: ..." with the given angle property. All we do for the first line of any proof is repeat what is given to us. It seems silly and redundant, but it is important. Whenever you do a proof you always start with what you're given (some fact or theorem already proven earlier) and you somehow try to connect it to what you are trying to prove.
Reason B: The angle addition postulate is essentially the idea where we break up an angle into smaller pieces. This is probably better shown in a visual style instead of using words. Have a look at the attached image. Notice how the green angle ABD and the red angle DBE combine to form the purple angle ABE. Hopefully the image is clear enough. If not, then feel free to ask any questions.
Reason C: We're using the substitution property here. If x = a and x = b, then we can say that a = b. That's what is going on but on a more complicated level.
Reason D: We subtract the quantity "measure of angle DBE" from both sides. It is like going from x+2 = y+2 to x = y (subtract 2 from both sides). This is the subtraction property of equality in action. In general the rule is if a = b, then a-c = b-c
Answer:
x=6
Step-by-step explanation:
5x+9-3x=21
5x-3x=21-9
2x=12
x=6
Answer:
u=6
Step-by-step explanation:
One rule in algebra is what you do to one side, you do it to other side. So if you multiply a number in one side, multiply the same number in other side. Here in this question, you are trying to find the value of the variable u. Variable is called so because the value of it varies depending on different question. Here u is going to be a constant number which when multipled by 3 and then subtracted by 3 equals 15.
So first step is we try to get constants on one side. So we add 3 on both sides to get rid of 3 on left.
3u - 3 + 3= 15+3
3u= 18
Now we divide by 3 on both sides to get u by itself.
3u/3 = 18/3
u= 6
Answer:
0.23 = 7/30
0.4 = 4/9
1.6 = 5/3
3.5 = 32/9
Step-by-step explanation:
I'm 100% that this is correct
Answer:
M(t) = M(16 - 2·t)
Step-by-step explanation:
The function is just formed by using the concept of composite functions.
B is cups of blueberries, and n is cups of blueberries,
So by substituting values the required equations formed are given by :
B(t) = 2·(8 - t)
M(n) = 12·n
n = B(t)
M(t) = M(n)
= M(B(t))
= M(2·(8 - t))
= M(16 - 2·t)
Therefore, this is the required function muffins M